Structural and functional analyses of hepatitis B virus X protein BH3-like domain and Bcl-xL interaction - Tian-Ying Zhang (Nature Portfolio, 2019)
Hepatitis B virus X protein (HBx) binds anti-apoptotic Bcl-xL through its BH3-like motif to promote viral replication. Here, the authors provide the structure of the HBx BH3-like domain and Bcl-xL, which shows an unusual mode of interaction, and identify a short peptide that inhibits HBV replication in cultured human hepatic cells.